The Error Analysis of the Complex Modulation for Flattop Focusing Beam Shaping - Shao, Jing; Dong, Hao; Han, Suli; Sun, Shufeng; Nie, Zhenwei (Frontiers in Physics, 2022)
In order to obtain a focusing flattop beam with high uniformity, complex modulation is used to modulate the optical pupil function, and the beam shaping algorithm is designed with a single phase-only Spatial Light Modulator (SLM). Actually, the wavefront aberrations introduced by each element reduce the uniformity of the shaped beam. In particular, the wavefront aberrations in different positions have different effects on this complex modulation algorithm. However, there is a lack of the corresponding error data and robustness analysis. Here, the error and robustness of the complex modulation algorithm are analyzed when different types of aberrations (defocus, astigmatism and coma) exist in different positions of the shaping optical system, and the Mixed Area Magnification Free (MRAF) algorithm is used as a reference for comparison. The results show that coma has the greatest effect on the beam shaping quality. It is also proved that the impact on the beam quality when there are aberrations in the laser and beam expansion system is greater than that in the SLM and the focusing lens for the complex modulation algorithm, which is different from the MRAF case.